2000
DOI: 10.1006/obhd.1999.2880
|View full text |Cite
|
Sign up to set email alerts
|

Examining Models of Nondominated Decoy Effects across Judgment and Choice

Abstract: Three experiments explored cognitive models of inferior, compromise, and phantom decoy effects in both judgment and choice. Participants made judgments of attractiveness, justifiability, and evaluation anxiety associated with each alternative in the set, along with judgments of the attractiveness of each alternative's dimensional values. In another session, they also chose the alternative they most preferred. Results were analyzed in terms of the degree to which decoy effects reflected shifts in dimensional va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
174
2
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 25 publications
11
174
2
7
Order By: Relevance
“…Research suggests that individuals are highly concerned with the justifiability of their decisions (Montgomery, 1983;Pettibone & Wedell, 2000;Simonson, 1989;Slovic, 1975;Tversky, 1972). This desire for decision justifiability can lead to violations of fundamental principles of rational decision making, such as procedural invariance and regularity, and, thus, to biased choices, as illustrated by the reason-based choice effects literature Simonson, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that individuals are highly concerned with the justifiability of their decisions (Montgomery, 1983;Pettibone & Wedell, 2000;Simonson, 1989;Slovic, 1975;Tversky, 1972). This desire for decision justifiability can lead to violations of fundamental principles of rational decision making, such as procedural invariance and regularity, and, thus, to biased choices, as illustrated by the reason-based choice effects literature Simonson, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Montgomery, 1983;Pettibone & Wedell, 2000;Simonson, 1989;Slovic, 1975;Tversky, 1972) have written about how the reasons and justifications the decision maker sees for and against the available alternatives influence decision making. Interestingly, the desire to make justifiable decisions can sometimes lead to choices that violate the norms of rational decision making (Barber, Heath, & Odean, 2003;Huber, Payne, & Puto, 1982;Simonson, 1989).…”
Section: Reason-based Choice Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study raises the possibility that other effects identified in the decision-making literature could also be extended to judgments about episodic memories. For example, in the compromise effect (e.g., Pettibone & Wedell, 2000;Simonson, 1989), a third option, E, representing a compromise between A and B (e.g., a mid-priced flight requiring two stops for the case in the Introduction) can be preferred in the ternary choice (ABE) even when it is not preferred in either binary choice (AE or BE). An interaction between the two processes of attention-switching and lateral inhibition can explain the compromise effect (see Roe et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, if you then were offered the choice of 50th-row seats for $150, not only would you reject that choice immediately but you may see the $100 tickets for the 50th row as a better choice than the front-row seats. Decoy effects have been documented in situations where human consumers evaluate products (e.g., Pettibone & Wedell, 2000;Wedell, 1991) and evaluate mate choices (Sedikides, Ariely, & Olsen, 1999). There is also evidence that animals may be affected by decoy stimuli (e.g., honeybees : Shafir, Waite, & Smith, 2002;hummingbirds: Bateson, Healy, & Hurly, 2002;Hurly & Oseen, 1999;starlings: Bateson, 2002;Schuck-Paim, Pompilio, & Kacelnik, 2004;cats: Scarpi, 2011).…”
Section: Biases and Context Effectsmentioning
confidence: 99%